The dialectic of orality and ideology in Wole Soyinka's Idanre and Ogun Abibiman (2013)
The paper fuses three concerns: the thematic, stylistic and ideological as a strategy of textual engagement. And it commences by arguing against the tendency to consider the oral and written as binary sets, as cultural moments in cartesian divide. It identifies such overlaps through the African experience in orality and writing by reechoing Nsibidi, the Ajami tradition, the Meroe-Kushitic and the Kemetic Medu-Netcher. This habit of reading is then demonstrated, in a broad sense, by examining the dialectic of orality and ideology in two of Wole Soyinka’s poems —Idanre and Ogun Abibiman. In specific terms, the conceptual essense ol die dialectic here compels a textual examination of both the intricate and interstitial as interconnected in oral literary devices, which are also embedded ideological forms.